“If you miss that first step in the chain of survival, there is no second step”–Emergency ambulance call-takers’ experiences in managing out-of-hospital cardiac arrest calls - Perera, Niru; Birnie, Tanya; Whiteside, Austin; Ball, Stephen; Finn, Judith (Public Library of Science (PLoS), 2023)
When a person has an out-of-hospital cardiac arrest (OHCA), calling the ambulance for help is the first link in the chain of survival. Ambulance call-takers guide the caller to perform life-saving interventions on the patient before the paramedics arrive at the scene, therefore, their actions, decisions and communication are integral to saving the patient’s life. In 2021, we conducted open-ended interviews with 10 ambulance call-takers with the aim of understanding their experiences of managing these phone calls; and to explore their views on using a standardised call protocol and triage system for OHCA calls. We took a realist/essentialist methodological approach and applied an inductive, semantic and reflexive thematic analysis to the interview data to yield four main themes expressed by the call-takers: 1) time-critical nature of OHCA calls; 2) the call-taking process; 3) caller management; 4) protecting the self. The study found that call-takers demonstrated deep reflection on their roles in, not only helping the patient, but also the callers and bystanders to manage a potentially distressing event. Call-takers expressed their confidence in using a structured call-taking process and noted the importance of skills and traits such as active listening, probing, empathy and intuition, based on experience, in order to supplement the use of a standardised system in managing the emergency. This study highlights the often under-acknowledged yet critical role of the ambulance call-taker in being the first member of an emergency medical service that is contacted in the event of an OHCA.